2010
DOI: 10.1111/j.1539-6924.2010.01544.x
|View full text |Cite
|
Sign up to set email alerts
|

How People Perceive and Will Cope with Risks from the Diffusion of Ubiquitous Information and Communication Technologies

Abstract: Information and communication technologies (ICTs) are increasingly pervasive and continue to reshape our environment. This trend carries different risks. Therefore, the early sensitization of people to these risks, as well as improving their capacity for protective coping behavior, is essential. Based on the protection motivation theory (PMT), we examined with structural equation modeling the relationships between different components of threat and coping appraisal to explain protective and nonprotective respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The previous IS research has shown that perceived benefits have a positive influence on the use of IT devices and applications ( Benlian & Hess, 2011 ; Gupta, Yousaf, & Mishra, 2020 ; Kim, Jang, & Yang, 2017 ; Moser, Bruppacher, & Mosler, 2011 ; Zhou, Jin, Fang, & Vogel, 2015 ). According to the CMUA, the perceived opportunity of an IT event fosters the adoption of benefits maximizing and benefits satisficing strategies ( Beaudry & Pinsonneault, 2005 ; Elie-Dit-Cosaque & Straub, 2011 ).…”
Section: Hypotheses Development and Research Modelmentioning
confidence: 99%
“…The previous IS research has shown that perceived benefits have a positive influence on the use of IT devices and applications ( Benlian & Hess, 2011 ; Gupta, Yousaf, & Mishra, 2020 ; Kim, Jang, & Yang, 2017 ; Moser, Bruppacher, & Mosler, 2011 ; Zhou, Jin, Fang, & Vogel, 2015 ). According to the CMUA, the perceived opportunity of an IT event fosters the adoption of benefits maximizing and benefits satisficing strategies ( Beaudry & Pinsonneault, 2005 ; Elie-Dit-Cosaque & Straub, 2011 ).…”
Section: Hypotheses Development and Research Modelmentioning
confidence: 99%
“…More recent research has extended it to the technology-related risk domain to study online privacy intrusion (Meso, Yi Ding, & Shuting Xu, 2013;Milne, Labrecque, & Cromer, 2009;Sangmi, Bagchi-Sen, Morrell, Rao, & Upadhyaya, 2009), identity theft (Lai, Li, & Hsieh, 2012), online spying and hacking (Chenoweth, Minch, & Gattiker, 2009) and other, broad I.T. threats (Liang & Xue, 2009;Moser, Bruppacher, & Mosler, 2011).…”
Section: Protection Motivation Theory On Facebook Privacymentioning
confidence: 99%
“…A modified framework based on the work by Rogers (1983) was produced by Moser et al (2011). Moser et al (2011) argued that anticipated personal susceptibility of risk may predict perceived threat, which influences both non-protective and protective responses to risks associated with information communication technology.…”
Section: Introductionmentioning
confidence: 99%
“…A modified framework based on the work by Rogers (1983) was produced by Moser et al (2011). Moser et al (2011) argued that anticipated personal susceptibility of risk may predict perceived threat, which influences both non-protective and protective responses to risks associated with information communication technology. Applicants may only be willing to tolerate an invasion of their privacy when doing so would protect vulnerable others such as children (see also Calvasina et al , 2008).…”
Section: Introductionmentioning
confidence: 99%